A clinical study on precancerous lesions of oral cavity in patients attending dental hospital, Telangana - Hanumakonda, Soundarya; Swetha, Marri; Bhashitha, Mallela; Mudigonda, Harsha (International Journal Of Community Medicine And Public Health, 2019)
Background: Aim of the retrospective study is to determine the type and frequency of the precancerous lesions of the oral cavity and to assess their sex, age distribution among the patients. Methods: Study was conducted based on year-wise data collected during 2015 to 2018 of all the patients with precancerous lesions of oral cavity. Results: The total number of patients was 1247, out of which 803 (64.39%) were males and 444 (35.60%) were females. Most common precancerous lesion is oral submucous fibrosis (70.24%) followed by oral lichen planus (19.08%), leukoplakia (8.98%), erythroplakia (1.68%). Conclusions: We observed marked geographical variation in the incidences of various precancerous lesions. Mostly males are affected by precancerous lesions than females.